How mandatory is the mandatory reporting of children at risk?. (1st November 2018) - Isaacs, David; Britton, Philip N; Kilham, Henry A; Bag, Shopna; Marks, Susan
Abstract: Although mandatory reporting of suspected child abuse was first introduced over 50 years ago, there are no quantitative studies addressing whether or not it achieves better outcomes for children. We report two cases of maternal infection, one with tuberculosis (TB) and one with human immunodeficiency virus (HIV), where the mothers' failure to attend follow‐up appointments raised the possibility of significant harm if their infants were infected. Some health professionals argued strongly that mandatory reporting meant the mothers should be reported to child protection authorities. Others argued that the risk was not critically imminent and an immediate report could seriously compromise maternal confidentiality, risked maternal disengagement and a worse outcome. An alternative was to make more vigorous efforts to contact the mothers and report only if these failed. In the TB case, reporting to child protection was deferred in favour of making more strenuous efforts at communication, which proved successful. In the HIV case, a case worker reported the case to child protection, but when the doctor contacted child protection authorities they agreed not to contact the mother unless the doctor's vigorous attempts to communicate with her failed. We do not advocate for breaking the law regarding mandatory reporting, but we do argue for a considered approach to the timing of reporting and for a collaborative approach with child protection services.